Is aspirin a substrate of MDR1/P-glycoprotein?. (2nd October 2020) - Singh, Renu; Naik, Tanvi; Nigam, Anuja; Chatterjee, Sagnik; Rajanna, Prabhakar; Shen, Hong; Iyer, Ramaswamy
Abstract: Aspirin (acetyl salicylic acid) is widely used co-medication in patients with cardiovascular and cerebrovascular diseases. Given the prevalence of acetyl salicylic acid's use as a co-medication and conflicting reports in the literature on it being a substrate of P-glycoprotein (P-gp). There is a potential risk for its interaction with compounds with P-gp liability, therefore, we have conducted a detailed investigation to determine substrate potential of acetyl salicylic acid towards P-gp. We observed significantly lower cellular uptake of acetyl salicylic acid in MDR1 transfected LLC-PK1 cells compared to LLC-PK1 wild-type (WT) cells, however, the in vitro efflux of acetyl salicylic acid in MDR1 transfected LLC-PK1 cells was not inhibited by known inhibitors under various conditions. Acetyl salicylic acid did not show active asymmetrical transport across MDR1 transfected LLC-PK1 cells compared to LLC-PK1-WT cells in transwell assay. Moreover, no difference in plasma and brain exposure of acetyl salicylic acid and its metabolite salicylic acid was observed between FVB-WT and Mdr1a/b knockout (KO) mice. Taken together, our findings indicate that acetyl salicylic acid is not a substrate of P-gp.